WOMEN AND LEADERSHIP IN ISLAMIC HIGHER EDUCATION IN INDONESIA - Safrul Muluk (Englisia: Journal of Language, Education, and Humanities, 2014)
In Indonesia, the issue of women in leadership position within public organizations, including in higher education, has been under scrutiny for a long time. Practices of patriarchal culture plays a significant role in the way people perceive women and their contribution have influenced the opportunity for female academics to assume senior leadership roles. Despite the increase in the number of well-educated women in higher education sector, it does not reflect in the number of women assuming leadership roles. This paper presents a brief historical account on higher education sector in Indonesia and then discusses women and leadership in higher education, with a special reference to State Islamic University Ar-Raniry Banda Aceh.